Nitrogen-doped activated carbon / graphene oxide composite material as well as preparation method and application thereof
The modified separators are prepared by nitrogen-doped activated carbon/graphene oxide composites, which solves the problems of shuttle effect and polysulfide dissolution in room-temperature sodium-sulfur batteries, improves electrochemical performance and cycle life, and simplifies the preparation process and reduces the cost.
Patent Information
- Application Number
- CN202310728397.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
AI Technical Summary
The existing room temperature sodium-sulfur batteries have shuttle effects and polysulfide dissolution problems in actual applications, resulting in insufficient electrochemical performance and cycle life. The existing modified separator preparation methods are complex, costly and dangerous, and are also very costly and have a large amount of MnO2 nanometers. The modified commercial diaphragm improves the cycle life of limited.
Using nitrogen-doped activated carbon/graphene oxide composite material as the modified separator material, nitrogen-doped activated carbon is obtained through annealing and heat treatment, and mixed with graphene oxide in a specific proportion to form a composite material with rich pore structure and active sites. , used to prepare modified diaphragms to suppress shuttle effects and improve electrochemical performance.
It significantly improves the utilization rate and electrochemical performance of the active material of room temperature sodium-sulfur batteries, improves the rate performance and cycling performance, and can maintain a high capacity level after 100 weeks of 0.1C cycle, and the preparation process is simple and the cost is relatively low.
Smart Images

Figure CN119160884A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of room temperature sodium-sulfur batteries, and in particular to a nitrogen-doped activated carbon / graphene oxide composite material, a modified diaphragm, and preparation methods and applications thereof. Background Art
[0002] The energy density of the most successful commercial lithium-ion batteries is as high as 200Wh kg -1 , but it can no longer meet the rapidly growing demand for energy storage. Room temperature sodium sulfur batteries have a higher theoretical energy density (1673Wh kg) than lithium-ion batteries. -1 ) has been widely studied and is considered to be the most promising alternative battery system. However, there are still many problems to be overcome before its practical application. For example, polysulfide dissolution and shuttle effect. In order to solve this problem, researchers have made great efforts to suppress the shuttle effect.
[0003] CN111540868A discloses a preparation method and application of a two-dimensional manganese dioxide modified polypropylene diaphragm, wherein manganese dioxide nanosheets are prepared using graphene oxide nanosheets as templates, and the modified diaphragm is prepared by vacuum filtration, and the sulfur barrier effect is significantly improved. However, the material preparation method is complex, costly and dangerous, and the improvement of the cycle life of the commercial diaphragm (Celgard 2500) modified by MnO2 nanosheets is also limited. Summary of the invention
[0004] The present invention provides a nitrogen-doped activated carbon / graphene oxide composite material and a preparation method and application thereof. A modified diaphragm is prepared based on the composite material prepared by the present invention, and the modified diaphragm is applied to a room temperature sodium-sulfur battery, which can effectively improve the utilization rate and electrochemical performance of the active material of the room temperature sodium-sulfur battery.
[0005] To achieve the purpose, the present invention provides the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a nitrogen-doped activated carbon / graphene oxide composite material, the preparation method comprising the following steps:
[0007] 1) heating the raw activated carbon to a first temperature in an inert atmosphere for annealing, wherein the first temperature is 100-800° C.; and obtaining nitrogen-doped activated carbon through the annealing;
[0008] 2) mixing the nitrogen-doped activated carbon obtained in step 1) with sodium hydroxide in a mass ratio of 1:0.5-1:2 (e.g., 1:0.5, 1:1, 1:1.5, 1:2, etc.), and heat treating at a second temperature under an inert atmosphere; then adding hydrochloric acid to consume the residual sodium hydroxide; the second temperature is 100-850° C.;
[0009] 3) mixing the nitrogen-doped activated carbon treated in step 2) with graphene oxide in a mass ratio of 9:0.5-9:1 (e.g., 9:0.5, 9:0.6, 9:0.7, 9:0.8, 9:0.9, 9:1, etc.) to obtain the composite material.
[0010] The above-mentioned preparation method of the present invention is used to prepare a nitrogen-doped activated carbon / graphene oxide composite material, the raw material activated carbon is annealed, then heat-treated with sodium hydroxide, and residual sodium hydroxide is removed with hydrochloric acid, and then combined with graphene oxide in a specific ratio. The obtained composite material is particularly suitable for modifying the diaphragm material of a room temperature sodium-sulfur battery. The diaphragm material modified based on the composite material of the present invention has a rich pore structure and active sites provided by nitrogen doping. The modified diaphragm material prepared based on the above-mentioned composite material is used in a room temperature sodium-sulfur battery, can effectively adsorb soluble polysulfides, can effectively inhibit the shuttle effect, is conducive to improving the utilization rate and electrochemical performance of the active material of the room temperature sodium-sulfur battery, can improve the rate performance and cycle performance, for example, after 100 cycles at 0.1C, it can still maintain a high capacity level.
[0011] In the present invention, the nitrogen-doped activated carbon treated in steps 1) and 2) is mixed with graphene oxide in a mass ratio of 9:0.5-9:1 to obtain a composite material. When the composite material of this ratio is subsequently used to modify the diaphragm substrate, a modified diaphragm with better performance can be obtained, and when the modified diaphragm is prepared by subsequent filtration (such as suction filtration), it is not easy to cause some nitrogen-doped activated carbon with smaller particle size to pass through the diaphragm substrate. More preferably, the mass ratio of the nitrogen-doped activated carbon to the graphene oxide is 9:0.7-9:1. The composite material obtained by using the preferred mass ratio is used to modify the diaphragm substrate, which is conducive to further improving the electrochemical performance of the room temperature sodium-sulfur battery based on the modified diaphragm material.
[0012] In a preferred embodiment, in step 1), the nitrogen doping amount in the nitrogen-doped activated carbon after annealing is 2-5% in atomic percentage, such as 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc. The inventors have found that controlling the nitrogen doping amount of the nitrogen-doped activated carbon in the composite material to 2-5% is conducive to obtaining a modified diaphragm with better application performance, which can further improve the electrochemical performance of the room temperature sodium-sulfur battery and obtain better rate performance and cycle performance. Preferably, the nitrogen doping amount in the nitrogen-doped activated carbon is 2.5-5%, more preferably 2.5-3.5%. In step 2), the activated carbon with the preferred nitrogen doping amount is used to prepare the composite material of the present invention, which is used to transform the diaphragm substrate, which is conducive to further improving the electrochemical performance of the room temperature sodium-sulfur battery based on the modified diaphragm material.
[0013] Furthermore, in step 1), the raw activated carbon is nitrogen-doped activated carbon, or the raw activated carbon carries nitrogen element and can form nitrogen-doped activated carbon after the annealing treatment; that is, nitrogen-doped activated carbon can be directly used as the raw activated carbon, or activated carbon carrying nitrogen element and can be formed into nitrogen-doped activated carbon after the annealing treatment in step 1) can be used as the raw activated carbon.
[0014] Preferably, in step 1), the raw activated carbon is waste activated carbon. The present invention can directly use waste activated carbon, for example, it can directly use waste activated carbon that has already formed nitrogen doping, or use activated carbon that carries nitrogen and can be formed into nitrogen doping through annealing treatment in step 1), wherein the nitrogen element is derived from melamine, nitrogen-containing salts, etc. carried in the waste activated carbon. Preferably, the activated carbon finally used in step 2) preferably has a nitrogen doping amount of 2-5% (atomic percentage). That is, preferably, the raw activated carbon in step 1) can be selected from such raw activated carbon that can obtain nitrogen doping amount that meets the requirement of 2-5% after annealing treatment in step 1), and those skilled in the art can make specific selections of activated carbon raw materials according to this requirement.
[0015] Furthermore, in step 1), if the raw activated carbon cannot be treated in step 1) to obtain nitrogen-doped activated carbon, a nitrogen doping agent is added to step (1) so that the raw activated carbon can obtain the nitrogen-doped activated carbon after being treated in step 1); preferably, the amount of the nitrogen doping agent is based on the nitrogen-doped activated carbon with a nitrogen doping amount of 2-5% that can be obtained in step 1). That is, the raw activated carbon in step 1) may also be activated carbon without nitrogen, or the nitrogen carried cannot enable the raw activated carbon to obtain nitrogen-doped activity or cannot obtain raw activated carbon that meets the nitrogen doping amount requirement through step 1), and such activated carbon may be waste activated carbon; in this case, the desired nitrogen-doped activated carbon may be obtained by adding a nitrogen doping agent in step 1). The nitrogen doping agent may be a corresponding reagent commonly used in the art for nitrogen doping, and there is no particular limitation on this, such as melamine, urea, trichloroethylamine, etc.
[0016] In the present invention, the waste activated carbon is first annealed at a first temperature, and the first temperature is 100-800° C. In a preferred embodiment, in step 1), the first temperature is 600-800° C. (for example, 600° C., 650° C., 700° C., 750° C., 800° C., etc.), and the annealing treatment is performed at a preferred treatment temperature, and then heat-treated with sodium hydroxide, etc. The composite material formed by the combination of nitrogen-doped activated carbon and graphene oxide obtained by such treatment is used to modify the diaphragm substrate, which can further improve its application performance in room temperature sodium-sulfur batteries, and is conducive to further improving the electrochemical performance of room temperature sodium-sulfur batteries.
[0017] In the present invention, after the activated carbon is annealed in step 1), it is mixed with sodium hydroxide in a mass ratio of 1:0.5-1:2 (more preferably 1:1-1:2) in step 2) and heat treated at 100-850°C. By treating the activated carbon through the above steps 1) and 2), not only can the impurities therein be removed, but also the activated carbon can be further pore-formed. The treated nitrogen-doped activated carbon has a higher specific surface area and a rich pore structure. In a preferred embodiment, in step 2), the second temperature is 600-800°C (for example, 600°C, 650°C, 700°C, 750°C, 800°C, etc.).
[0018] In a preferred embodiment, in step 1), the holding time at the first temperature is 1-8 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc.
[0019] In a preferred embodiment, in step 2), the heat treatment time is 1-6 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, etc.
[0020] In step 2), the purpose of adding hydrochloric acid is to remove residual sodium hydroxide, and the specific amount of hydrochloric acid is based on the amount of residual sodium hydroxide that can be removed, and there is no particular limitation on this. In some embodiments, in step 2), the molar ratio of the amount of hydrochloric acid used in terms of HCl to the amount of sodium hydroxide used is 0.5-1:1.
[0021] Specifically, the inert atmosphere in step 1) and step 2) is, for example but not limited to, argon atmosphere.
[0022] The nitrogen-doped activated carbon / graphene oxide composite material is prepared by the preparation method of the present invention. First, the activated carbon is annealed, and then mixed with sodium hydroxide in a specific mass ratio for heat treatment. Then, the treated nitrogen-doped activated carbon and graphene oxide are combined in a mass ratio of 9:0.5-9:1 to form a composite material. The composite material has a three-dimensional porous structure, a rich pore structure and a large specific surface area, and also has nitrogen-doped active sites. The composite material is used to modify the diaphragm material used in the room temperature sodium-sulfur battery, can effectively adsorb soluble polysulfides, can improve the electrochemical performance of the room temperature sodium-sulfur battery, has a better first coulomb efficiency, and can improve the rate performance and cycle performance.
[0023] In some more preferred embodiments, the nitrogen doping amount in the nitrogen-doped activated carbon obtained in step 1) is 2.5-5%, preferably 2.5-3.5%; the mass ratio of the nitrogen-doped activated carbon and the sodium hydroxide in step 2) is 1:1-1:2; the mass ratio of the nitrogen-doped activated carbon and the graphene oxide in step 3) is 9:0.7-9:1; the first temperature in step 1) is 600-800°C, and the second temperature in step 2) is 600-800°C. The inventors have found that the composite material obtained by adopting this preferred embodiment is used to transform the diaphragm substrate, which can obtain better comprehensive performance, can take into account higher discharge capacity and first efficiency, and has better cycle performance; in this preferred embodiment, the nitrogen-doped activated carbon with a nitrogen doping amount of 2.5-3.5% in step 1) is beneficial to further improve the comprehensive electrochemical performance.
[0024] Another aspect of the present invention further provides a nitrogen-doped activated carbon / graphene oxide composite material prepared by the preparation method described above.
[0025] In another aspect, the present invention further provides a modified diaphragm for a room temperature sodium-sulfur battery, the modified diaphragm comprising a diaphragm substrate, the diaphragm substrate being loaded with the nitrogen-doped activated carbon / graphene oxide composite material as described above. The modified diaphragm is applied to a room temperature sodium-sulfur battery, can significantly improve the adsorption of soluble polysulfides, can significantly improve the inhibition of the shuttle effect, is conducive to improving the utilization rate and electrochemical performance of active materials in the room temperature sodium-sulfur battery, improves the rate performance and cycle performance, for example, after 100 cycles at 0.1C, it can still maintain a high capacity level.
[0026] Preferably, the membrane substrate is a glass fiber membrane, and the glass fiber membrane can be directly a commercially available product, such as but not limited to Whatman GF / C 1822-090.
[0027] In some preferred embodiments, the loading amount of the nitrogen-doped activated carbon / graphene oxide composite material on the diaphragm substrate is 0.21-0.85 mg / cm 2 .
[0028] Another aspect of the present invention provides a method for preparing the modified diaphragm described above, comprising the following steps:
[0029] The nitrogen-doped activated carbon / graphene oxide composite material is dispersed in a solvent to obtain a suspension; the suspension is filtered using the diaphragm substrate as a filter material, so that the solvent in the suspension is filtered through the diaphragm substrate, so that the nitrogen-doped activated carbon / graphene oxide composite material in the suspension is loaded on the diaphragm substrate, and the modified diaphragm is obtained after drying.
[0030] Preferably, the filtration is performed by suction filtration.
[0031] There is no particular restriction on the solvent used for the above-mentioned dispersion, so long as good dispersion of the composite material can be achieved. Preferably, the solvent is an ethanol solution, and there is no particular requirement for the concentration of the ethanol solution. In some embodiments, a 90 wt % or more ethanol aqueous solution is used, specifically, for example, a 95 wt % ethanol aqueous solution.
[0032] Preferably, the drying is vacuum drying.
[0033] The preparation method of the modified diaphragm of the present invention has a simple preparation process, and the desired modified diaphragm material can be obtained by simple filtration (preferably suction filtration) and drying. The prepared modified diaphragm has better application performance in room temperature sodium-sulfur batteries, can effectively adsorb soluble polysulfides, can improve the capacity, rate performance and cycle performance of room temperature sodium-sulfur batteries, and can further promote the practical application of room temperature sodium-sulfur batteries.
[0034] The present invention also provides the use of the modified diaphragm described above or the modified diaphragm prepared by the preparation method described above in a room temperature sodium-sulfur battery.
[0035] The technical solution provided by the present invention has the following beneficial effects:
[0036] 1. The present invention uses activated carbon, especially waste activated carbon, as raw material, anneals it, mixes it with sodium hydroxide, and then performs heat treatment, and then combines it with graphene oxide to form a composite material. The composite material is particularly suitable for modifying the diaphragm material in room temperature sodium sulfur batteries, can effectively adsorb soluble polysulfides, effectively inhibit the shuttle effect, and is conducive to improving the utilization rate and electrochemical performance of active materials in room temperature sodium sulfur batteries. It has a better first coulomb efficiency and can improve the rate performance and cycle performance. At the same time, it can also improve the utilization value of waste activated carbon.
[0037] 2. The modified diaphragm provided by the present invention has a simple preparation process. The modified diaphragm is applied to room temperature sodium-sulfur batteries, which can improve the utilization rate and electrochemical properties of active materials in room temperature sodium-sulfur batteries, and improve rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Shown is the BET test result of the activated carbon treated in step 2) in Example 1;
[0039] Figure 2 Shown is the average pore size test result of the activated carbon after being treated in step 2) in Example 1;
[0040] Figure 3 Shown are the morphological characterization results of the modified glass fiber diaphragm surface;
[0041] Figure 4 Shown are the morphological characterization results of the treated waste activated carbon. DETAILED DESCRIPTION
[0042] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0043] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.
[0044] The test method involved in the embodiment is introduced below:
[0045] 1. Pore structure test
[0046] Test equipment: BET and pore structure analysis were performed on a Micromeretics ASAP 2010 analyzer. Test conditions: N2 was used as the adsorbate, adsorption was performed at liquid nitrogen temperature (77K), and the specific surface area was determined by the BET method, with a linear range of P / P0 = 0.05-0.3, where P0 is the saturated vapor pressure of the adsorbate at the experimental temperature, and P is the equilibrium pressure during adsorption. Test steps: After degassing at 300°C for 3h, BET test was performed.
[0047] 2. Morphology characterization
[0048] Test equipment: The test was carried out in a JEOL JEM-ARN 200F spherical aberration corrected transmission electron microscope.
[0049] Test conditions: Take an appropriate amount of sample (about 0.001g) and put it into a sample tube containing 3 ml of ethanol solution and shake it evenly. Put it into an ultrasonic cleaner for ultrasonic treatment for 0.5h, then use a capillary to absorb the solution after ultrasound, put it on a transmission carbon film, and after drying, you can test it.
[0050] 3. Application performance testing
[0051] In the following examples and comparative examples, the diaphragm materials are assembled into room temperature sodium-sulfur batteries for performance testing, wherein the room temperature sodium-sulfur batteries are button-type batteries, and the specific assembly process of the room temperature sodium-sulfur batteries is carried out in a conventional manner, except that the diaphragm materials therein are the corresponding diaphragm materials in each example or comparative example. Specifically, the preparation process of the button-type battery is as follows:
[0052] The nitrogen-doped activated carbon / sulfur composite material (nitrogen-doped activated carbon and sulfur are mixed and ground in a mass ratio of 7:1 for 0.5 hours, then put into a crucible, and then put into a tube furnace, and keep at 155°C for 12 hours under argon protection, and naturally cool to room temperature to obtain the composite material, wherein the nitrogen doping amount of the nitrogen-doped activated carbon is 3% by atomic percentage) is used as a positive electrode material and mixed with conductive carbon black Super P and binder polyvinylidene fluoride (PVDF) in a mass ratio of 80:10:10, and the solvent N-methylpyrrolidone (NMP) (about 65wt%) is added and stirred to form a uniform positive electrode slurry, and the positive electrode slurry is evenly coated on aluminum foil by a coating machine, and vacuum dried to obtain a positive electrode sheet. The obtained positive electrode sheet is cut into a circular electrode sheet with a diameter of 12 mm and placed in an MBraun 2000 glove box (Ar atmosphere, H2O and O2 concentrations less than 0.1×10 -6 Volume %) for standby. A circular pole piece is used as the positive electrode, a metal sodium sheet is used as the reference electrode, the diaphragm material of each embodiment or comparative example is used as the diaphragm, and a 1M NaClO4 solution (the solvent is a mixed solvent with a volume ratio of DEC (diethyl carbonate): EC (ethylene carbonate) = 1:1) is used as the electrolyte to assemble into a button battery. The 0.5C discharge capacity, the first coulomb efficiency and the capacity after 100 cycles of 0.1C of the button battery are tested. The battery capacity and the first efficiency are charged and discharged by the battery tester CT2001A of Wuhan Blue Electric Electronics Co., Ltd., with a current of 0.1C (1C = 1675mAh / g) and a voltage of 1.7-2.8V. The test results are summarized in Table 2.
[0053] Example 1: Composite material loading of 0.21 mg cm -2 Modified diaphragm (N-AC / GO+GF)
[0054] 1.1. Prepare nitrogen-doped activated carbon / graphene oxide composite materials according to the following steps:
[0055] 1) The waste activated carbon (specific surface area of 887m 2 g -1 , the average pore size is 1.97nm, and the salt compound containing nitrogen element is carried out annealing treatment in argon atmosphere, specifically, the temperature is first raised to 700℃ (first temperature), maintained for 5h (i.e. "maintaining time" in Table 1), and then annealed. The nitrogen doping amount in the activated carbon after step 1) is 3% (atomic percentage).
[0056] 2) The activated carbon treated in step 1) is mixed with sodium hydroxide in a mass ratio of 1:1.5, and heat treated at 750°C (heat treatment temperature) for 2 hours under an argon atmosphere; then 1M hydrochloric acid is added and mixed to consume the residual sodium hydroxide, and the molar ratio of the amount of hydrochloric acid added is 0.6:1 as calculated by HCl to the sodium hydroxide.
[0057] The nitrogen-doped activated carbon treated in step 2) was subjected to pore structure test and morphology characterization, and its specific surface area was 1303.9 m 2 g -1 , the average pore size is 2.2nm, for specific results see Figure 1 , 2 The morphology characterization results can be found in Figure 4 As can be seen from the figure, the nitrogen-doped activated carbon obtained through steps 1) and 2) has a rich pore structure, which corresponds to the experimental results of nitrogen adsorption and desorption.
[0058] 3) The activated carbon treated in step 2) is mixed with graphene oxide in a mass ratio of 9:1 to obtain a nitrogen-doped activated carbon / graphene oxide composite material (hereinafter referred to as "composite material").
[0059] 1.2. Prepare the modified diaphragm according to the following steps:
[0060] Add an appropriate amount of the composite material prepared in 1.1 to a 95wt% ethanol aqueous solution. The amount of ethanol aqueous solution used is 100ml relative to 10mg of the composite material. Perform ultrasonic treatment at room temperature for 0.5 hours to obtain a well-dispersed suspension. Add the suspension to a sand core filter device, which uses a glass fiber diaphragm as filter paper. Start the vacuum pump switch for suction filtration, filter until the liquid in the sand core filter device is drained, and then filter for about 30 seconds. At this time, a glass fiber diaphragm loaded with composite materials is obtained. Take it out, put it in a vacuum drying oven, and dry it at 60°C for 24 hours to obtain an N-AC / GO+GF diaphragm, in which the composite material loading is 0.21mg cm -2 .
[0061] The morphology of the modified membrane was characterized. Figure 3 As shown in the figure, it can be seen that the surface of the modified diaphragm is covered by a mixture of treated activated carbon and graphite oxide, but at the same time there are more pores, which is conducive to the penetration of electrolyte and the passage of ions and will not hinder the reaction kinetics.
[0062] Example 2: Composite material loading of 0.56 mg cm -2 Modified diaphragm (N-AC / GO+GF)
[0063] The method was carried out in accordance with Example 1, except that the amount of the composite material in 1.2 was changed so that the final composite material loading was 0.56 mg cm -2 N-AC / GO+GF separator.
[0064] Example 3: Composite material loading of 0.85 mg cm -2 Modified diaphragm (N-AC / GO+GF)
[0065] The method was carried out in accordance with Example 1, except that the amount of the composite material in 1.2 was changed so that the final composite material loading was 0.85 mg cm -2 N-AC / GO+GF separator.
[0066] Embodiment 4-5
[0067] The method is carried out in accordance with Example 1, except that some process conditions or amounts of substances in 1.1 are different. See Table 1 below for details:
[0068] Table 1
[0069]
[0070]
[0071] Comparative Example 1
[0072] The glass fiber separator (i.e., pure GF) used in Example 1 was directly used as the separator of the room temperature sodium-sulfur battery to carry out the aforementioned application performance test.
[0073] Comparative Example 2
[0074] A modified membrane was prepared with reference to Example 1, except that no composite material was used, but the glass fiber membrane was directly modified with the graphene oxide used in Example 1. Specifically, the operation of 1.2 in Example 1 was performed with reference to the operation of 1.2 in Example 1, except that the composite material was replaced with graphene oxide. The obtained modified membrane was recorded as "GO+GF".
[0075] Comparative Example 3
[0076] The modified diaphragm was prepared with reference to Example 1, except that: instead of using a composite material, the glass fiber diaphragm was directly modified with activated carbon that was not doped with nitrogen. Specifically, when preparing the composite material, waste activated carbon that did not carry nitrogen was used in step 1), and activated carbon that was not doped with nitrogen was obtained after treatment in step 1). The remaining steps were carried out with reference to Example 1. The resulting modified diaphragm was recorded as "AC+GF".
[0077] Comparative Example 4
[0078] A modified membrane was prepared with reference to Example 1, except that the composite material was not used, but the glass fiber membrane was modified with glucose-derived carbon. Specifically, the operation of 1.2 in Example 1 was performed with reference to the operation of 1.2 in Example 1, except that the composite material was replaced with glucose-derived carbon. The obtained modified membrane was recorded as "glucose-derived carbon + GF".
[0079] Among them, glucose-derived carbon is prepared by the following steps: weigh a certain amount of glucose (manufacturer: Aladdin, CAS: 50-99-7, purity: analytical grade) and put it into a cleaned corundum crucible, then put the crucible into a tubular furnace, and under the protection of inert gas, heat it to 800°C at a heating rate of about 2°C / min, and then keep it warm for 3 hours. After the tubular furnace is naturally cooled to room temperature, the crucible is taken out of the tubular furnace to obtain the glucose-derived carbon material.
[0080] Comparative Example 5
[0081] The modified diaphragm was prepared with reference to Example 1, except that when preparing the composite material, the annealing treatment in step 1) was omitted, and the heat treatment in step 2) was directly performed, and the remaining operations were the same as in Example 1.
[0082] Comparative Example 6
[0083] The modified diaphragm was prepared with reference to Example 1, except that when preparing the composite material, the mass ratio of nitrogen-doped activated carbon to graphene oxide in step 3) was 9:0.1. The remaining operations were the same as in Example 1.
[0084] Table 2
[0085]
[0086]
[0087] From the experimental results in Table 2, it can be seen that the composite material obtained by the embodiment of the preparation method of the present invention is used to modify the diaphragm compared with the composite material obtained in the comparative example. The modified diaphragm has better application performance in room temperature sodium-sulfur batteries, can improve the electrochemical performance of room temperature sodium-sulfur batteries, and takes into account higher discharge capacity, first coulomb efficiency and cycle performance. It can maintain a higher capacity after 100 cycles at 0.1C.
[0088] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A method for preparing a nitrogen-doped activated carbon / graphene oxide composite material, characterized in that: The preparation method comprises the following steps: 1) heating the raw activated carbon to a first temperature in an inert atmosphere for annealing, wherein the first temperature is 100-800° C.; obtaining nitrogen-doped activated carbon through the annealing, wherein the nitrogen doping amount in the nitrogen-doped activated carbon is preferably 2-5% by atomic percentage, more preferably 2.5-5%, and further preferably 2.5-3.5%; 2) mixing the nitrogen-doped activated carbon obtained in step 1) with sodium hydroxide in a mass ratio of 1:0.5-1:2, and heat-treating at a second temperature under an inert atmosphere; then adding hydrochloric acid to consume the residual sodium hydroxide; the second temperature is 100-850° C.; 3) mixing the nitrogen-doped activated carbon treated in step 2) with graphene oxide in a mass ratio of 9:0.5-9:1, preferably 9:0.7-9:1, to obtain the composite material.
2. The preparation method according to claim 1, characterized in that: In step 1), the raw activated carbon is nitrogen-doped activated carbon, or the raw activated carbon carries nitrogen and can form nitrogen-doped activated carbon after the annealing treatment; Alternatively, when the raw activated carbon cannot be treated in step 1) to obtain nitrogen-doped activated carbon, a nitrogen doping agent is added to step (1) so that the raw activated carbon can be treated in step 1) to obtain the nitrogen-doped activated carbon; preferably, the amount of the nitrogen doping agent is based on the amount of nitrogen doped activated carbon that can be obtained in step 1) with a nitrogen doping amount of 2-5%; Preferably, in step 1), the raw activated carbon is waste activated carbon.
3. The preparation method according to claim 1, characterized in that: In step 1), the first temperature is 600-800°C; And / or, in step 2), the second temperature is 600-800°C; And / or, in step 1), the first temperature is maintained for 1-8 hours; And / or, in step 2), the heat treatment time is 1-6 hours.
4. The preparation method according to claim 3, characterized in that: The nitrogen doping amount of the nitrogen-doped activated carbon obtained in step 1) is 2.5-5%, preferably 2.5-3.5%; The mass ratio of the nitrogen-doped activated carbon to the sodium hydroxide in step 2) is 1:1-1:2; The mass ratio of the nitrogen-doped activated carbon to the graphene oxide in step 3) is 9:0.7-9:1; In step 1), the first temperature is 600-800°C, and in step 2), the second temperature is 600-800°C.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step 2), the molar ratio of the amount of the hydrochloric acid (calculated as HCl) to the amount of the sodium hydroxide is 0.5-1:
1.
6. A nitrogen-doped activated carbon / graphene oxide composite material prepared by the preparation method according to any one of claims 1 to 5.
7. A modified diaphragm for room temperature sodium-sulfur battery, characterized in that: The modified diaphragm comprises a diaphragm substrate, on which the nitrogen-doped activated carbon / graphene oxide composite material according to claim 6 is loaded.
8. The modified diaphragm according to claim 7, characterized in that: The diaphragm substrate is a glass fiber diaphragm; Preferably, the loading amount of the nitrogen-doped activated carbon / graphene oxide composite material on the diaphragm substrate is 0.21-0.85 mg / cm 2 .
9. The method for preparing the modified diaphragm according to claim 7 or 8, characterized in that: The steps include: Dispersing the nitrogen-doped activated carbon / graphene oxide composite material in a solvent to obtain a suspension; filtering the suspension using the diaphragm substrate as a filter material, allowing the solvent in the suspension to filter through the diaphragm substrate, so that the nitrogen-doped activated carbon / graphene oxide composite material in the suspension is loaded on the diaphragm substrate, and obtaining the modified diaphragm after drying; Preferably, the filtering is performed by suction filtration; Preferably, the solvent is an ethanol solution; Preferably, the drying is vacuum drying.
10. Use of the modified diaphragm according to any one of claims 7 to 8 or the modified diaphragm prepared by the preparation method according to claim 9 in a room temperature sodium-sulfur battery.
Citation Information
Patent Citations
Preparation method of room-temperature sodium-sulfur battery diaphragm
CN112864526A
Preparation method and application of graphene oxide improved activated carbon
CN113750967A
Nitrogen-doped carbon nanomaterial as well as preparation method and related application thereof
CN115385325A
Sulfo group-containing graphene oxide, solid polymer electrolyte membrane, membrane electrode assembly, and method for manufacturing solid polymer fuel cell
JP2020066557A
Composite carbon material, and preparation method therefor and application thereof
WO2019218504A1
